Chronotherapy for patients with a depressive episode treated in a public outpatient mental healthcare clinic in Norway: protocol for a randomised controlled trial - Stian Lydersen; Håvard Kallestad; Gunnar Morken; Simen Saksvik; Knut Langsrud; Lina Stålesen Ramfjord; Nikolaj Kahn; Joar Øveraas Øveraas Halvorsen; Liv Sigrun Sættem Engvik (BMJ Open)
Introduction Depression is highly prevalent in outpatients receiving treatment for mental disorders. Treatment as usual (TAU) usually consists of either psychotherapy and/or antidepressant medication and often takes several weeks before clinical effect. Chronotherapy, consisting of sleep deprivation, sleep-wake phase advancement and stabilisation, and light therapy, is a possible addition to TAU that may decrease the time to treatment response. This randomised controlled trial will examine the benefits of adding chronotherapy to TAU compared with TAU alone.Methods and analysis The trial will include 76 participants with a depressive episode who initiate outpatient treatment at a secondary mental healthcare outpatient clinic at St. Olavs University Hospital. Participants will be randomly allocated 1:1 to either chronotherapy in addition to TAU or TAU alone. Assessments will be performed at baseline, day 3, day 4, day 7, day 14 and weeks 4, 8, 24 and 52, in addition to longer-term follow ups. The main outcome is difference in levels of depressive symptoms after week 1 using the Inventory of Depressive Symptomatology Self-Report. Secondary outcomes include levels of depressive symptoms at other time points, as well as anxiety, health-related quality of life and sleep assessed through subjective and objective measures.Ethics and dissemination The study protocol has been approved by the Regional Committee for Medical Research Ethics Central Norway (ref: 480812) and preregistered at ClinicalTrials.gov (ref: NCT05691647). Results will be published via peer-reviewed publications, presentations at research conferences and presentations for clinicians and other relevant groups. The main outcomes will be provided separately from exploratory analysis.Trial registration number NCT05691647.